(untitled) (International Journal of Mathematics and Physics, 2026)
Gimbaled thrust vector control (TVC) systems are widely employed in modern launch vehicles to provide attitude control during powered flight. However, the aerodynamic influence of the circumferential geometric discontinuity introduced by the gimbal joint gap on nozzle internal and external flow remains insufficiently studied in open literature. The purpose of this study is to evaluate aerodynamic losses and flow field modifications of bell-shaped rocket nozzles with the presence of a gimbal joint gap using computational fluid dynamics (CFD) simulation. These calculations were done using the Reynolds-Averaged Navier–Stokes (RANS) model in 2D axisymmetric flow in ANSYS Fluent software. For modelling the flow properties in compressible separated flows, the k-ω SST turbulence model was selected. Two nozzle configurations, with and without the gap of the gimbal joint, were compared. The Sutherland viscosity law and the NASA polynomial thermodynamic data were used for the working fluid and it was modeled as an ideal compressible gas representative of the combustion products of LOX/Kerosene. The exit to throat area expansion ratio for nozzle geometry is 8.97, which means that the nozzle is designed to have a supersonic exit condition. The CFD results showed a good agreement with the theoretical results, showing the validity of the numerical approach. The nozzle studied here operates under overexpanded conditions at sea level, where the nozzle exit static pressure falls below ambient pressure, giving rise to oblique shock waves in the exhaust plume and making the accurate characterisation of flow disturbances particularly important. The presence of the gimbal joint gap was found to introduce aerodynamic losses in Mach number of 6.74%, providing quantitative design-relevant data for gimbaled nozzle systems in launch vehicles. Keywords: gimbal joint gap, bell nozzle, TVC, CFD.